2022
DOI: 10.1186/s13578-022-00873-9
|View full text |Cite
|
Sign up to set email alerts
|

Unraveled roles of Cav1.2 in proliferation and stemness of ameloblastoma

Abstract: Background Transcriptome analysis has been known as a functional tool for cancer research recently. Mounting evidence indicated that calcium signaling plays several key roles in cancer progression. Despite numerous studies examining calcium signaling in cancer, calcium signaling studies in ameloblastoma are limited. Results In the present study, comparative transcriptome profiling of two representative odontogenic lesions, ameloblastoma and odontog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…The activation of the canonical Wnt signaling pathway prevents β‐catenin from being degraded via ubiquitination and causes it to accumulate in the nucleus, where it promotes the transcription of target genes such as MYC , CCND1 , and AXIN2 (Kikuchi et al, 2011). It has been reported that activation of the canonical Wnt pathway promotes the migration and invasion of AM cells (S. Liu et al, 2021) and the tumorigenicity and stemness of the immortalized AM cell line AM‐1 (Li et al, 2022). However, as our results showed, β‐catenin did not accumulate in the nucleus in AM cells, suggesting that the canonical Wnt pathway was not constitutively activated in AM cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the canonical Wnt signaling pathway prevents β‐catenin from being degraded via ubiquitination and causes it to accumulate in the nucleus, where it promotes the transcription of target genes such as MYC , CCND1 , and AXIN2 (Kikuchi et al, 2011). It has been reported that activation of the canonical Wnt pathway promotes the migration and invasion of AM cells (S. Liu et al, 2021) and the tumorigenicity and stemness of the immortalized AM cell line AM‐1 (Li et al, 2022). However, as our results showed, β‐catenin did not accumulate in the nucleus in AM cells, suggesting that the canonical Wnt pathway was not constitutively activated in AM cells.…”
Section: Discussionmentioning
confidence: 99%